Adult-Onset Still's Disease: From Pathophysiology to Targeted Therapies. (26th June 2012) - Mavragani, Clio P.; Spyridakis, Evangelos G.; Koutsilieris, Michael
Abstract : Adult-onset Still's disease (AOSD) is a systemic inflammatory disorder affecting primarily young individuals. The diagnosis is primarily clinical and necessitates the exclusion of a wide range of mimicking disorders. Given the lack of solid data in regard to the underlying pathogenetic mechanisms, treatment of AOSD has been for years largely empirical. Recent advances have revealed a pivotal role of several proinflammatory cytokines such as tumor necrosis factor- α (TNF- α ), interleukin-1 (IL-1), interleukin-6 (IL-6), interleukin-8 (IL-8), and interleukin-18 (IL-18) in disease pathogenesis, giving rise to the development of new targeted therapies aiming at optimal disease control.